A study of factors influencing academic performance of undergraduate medical students - Priyanka; Manish Kumar Goel; Sanjeev Kumar Rasania (Wolters Kluwer Medknow Publications, 2020)
Introduction: An important indicator of quality of medical education is students' academic performance and the study of factors which influence the academic performance of medical students is important as it can provide information to improve educational programs. Material and Methods: This was a cross-sectional study involving medical students who passed their final professional examinations and were about to start their internship training. They were asked to complete an anonymously administered feedback form which contained questions regarding the academic performance of students in all the professional examinations of MBBS along with background characteristics of students. Data entry and statistical analysis was carried out using statistical software SPSS version 12. The primary outcome was the proportion of students in different levels of academic achievement. The secondary outcome was the factors associated with different levels of academic achievement. Descriptive statistics were used to describe the distribution of all variables. For finding out the association, an analysis using Chi-square test was done for qualitative data. Results: The mean age of participants was 22.7 ± 0.67 years (range 21-25). About 43.6% of the students had scored <60% marks, while 56.4% had scored more than that. High-performing students were found to spend more time on hobbies as well as on physical activities and less time on social networking sites as compared to the average-performing students. Study and sleep habits of high performers were significantly different from average performers. Conclusion: Many factors were found to have a significant association with academic performance of students such as residence, having a doctor parent, spending time on personal hobbies and social networking sites, time spent on study, and duration of sleep a day before examination.